Simulation of Carrier Injection Efficiency in AlGaN-Based UV-Light-Emitting Diodes - Gregor Hofmann; Anton Muhin; Norman Susilo; Friedhard Romer; Tim Wernicke; Michael Kneissl; Bernd Witzigmann (IEEE Photonics Journal)
Numerical simulations of carrier transport in aluminium gallium nitride based ultraviolet light emitting diodes (UV-LED) are performed in order to understand injection efficiency for light sources in the deep ultraviolet. With our simulator, calibrated with experimental data from a 265 nm UV-LED, quantum efficiencies have been analyzed. The maximum internal quantum efficiency (IQE) of 30% consists of the product from radiative recombination efficiency (RRE) of 60% and carrier injection efficiency (CIE) of 50%. It is found that poor hole injection into the active region and a surplus of electrons limit both efficiencies, and leads to significant electron leakage into the p-side. This leakage is bias dependent, and has a minimum at maximum IQE. Further simulations show that distributed polarization doping (DPD) could improve carrier injection efficiency.